Enhancement of Cocoa Quality By the Indigenous Yeast Candida Tropicalis KLK4 Through Cocoa Bean Fermentation - Yanti, Nur Arfa (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
An indigenous yeast strain that isolated from fermented cocoa bean has a role in cocoa bean fermentation process, was characterized and identified to be member of the Candida tropicalis species based on phenotypic characteristics and the D1/D2 region of the large subunit rRNA gene. Properties of importance for cocoa bean fermentation, namely sucrose, glucose, and citrate assimilation capacity, pH-, ethanol-, and heat-tolerance, were examined for isolate. The Quality of fermented cocoa bean was analyzed by cut test. Candida tropicalis KLK4 was tolerance to low pH value, high temperature, ethanol and could assimilate citrate, reflecting it is able to adapt to cocoa fermentation environment. The utilization of Candida tropicalis KLK4 strain as a starter culture for cocoa fermentation can enhance cocoa quality.